Proyecto de Rehabilitación Patrimonial, Caso Conjunto Misión Josefina, Santa Clara, Provincia de Pastaza - Romero Coyago, Jocelyne Deyanira (2023)
The present research addresses the importance of the cultural heritage built in the Santa Clara canton, taking the "Misión Josefina" complex as a case study. This complex was the first religious settlement where health, spiritual, and educational buildings were built. This research approach is based on a graphic analysis and, with the help of concepts in rehabilitation and enhancement, is oriented towards the conservation of built heritageConservation strategies are proposed for the "Ernesto Ophuls" hospital and the "Our Lady of Agua Santa" church, built heritage of the canton. These strategies are divided into three levels of intervention: Liberation, constructive rehabilitation, and enhancement, the same ones that will help us give the building a new opportunity to be necessary for the canton, recovering the importance it had in the past. Currently, both the hospital and the church have fallen into abandonment and neglect; despite their significant architectural and historical wealth, these buildings are living testimonies of the urban growth and development of the canton